The effect of intellectual capital and strategic partnerships in construction companies - Sucena, A.; Matos, F.; Nunes, A. (Managerial Finance, 2025)
Purpose The construction industry is facing significant challenges due to globalization, increasing competition, and rapid technological advancements. In this context, intellectual capital and strategic partnerships have emerged as essential factors for the success and competitiveness of construction companies. Intellectual capital encompasses a company’s intangible assets, such as knowledge, skills, experience, expertise, and relationships. At the same time, strategic partnerships involve a mutually beneficial relationship between two or more organizations that work together to achieve common goals. Design/methodology/approach This article utilizes a statistical approach to analyze the variables in question through Structural Equation Modeling (SEM). The proposed hypothesis was evaluated using this method. Data were gathered through a questionnaire distributed to 88 individuals in managerial positions at small and medium-sized enterprises (SMEs) in the construction industry. Findings The findings suggest that intellectual capital and strategic partnerships can significantly improve construction companies’ innovation, efficiency, and competitiveness. However, effective management and utilization of these assets require a clear understanding of the company’s goals, resources, and capabilities, as well as the development of a collaborative and knowledge-sharing culture. The paper concludes by proposing future research directions and practical implications for construction companies to enhance their intellectual capital and strategic partnerships. Originality/value This paper aims to explore the effect of intellectual capital and strategic partnerships on the performance and competitiveness of construction companies, to offer insights into how construction companies can improve their performance and maintain competitiveness in a rapidly evolving environment.